IMPLEMENTASI KEBIJAKAN BELAJAR DARI RUMAH DENGAN TATANAN NORMAL BARU PADA SEKOLAH DASAR DI KECAMATAN BULAK KOTA SURABAYA - Nathasia May Afistha; Ananta Prathama (Universitas Halu Oleo, 2021)
The spread of COVID-19 in Indonesia is increasing every day. urged the government to immediately deal with the COVID-19 pandemic by making various policies such as implementing a lockdown, social distancing, physical distancing, self-isolation and Large-Scale Social Restrictions (PSBB). With this government policy, it certainly has a big impact in various aspects of life, especially in the aspect of education in Indonesia. With the implementation of PSBB, it encourages the government to issue policies on the implementation of education in Indonesia, because after all the learning process must continue so that the objectives of education can be achieved as a whole. The purpose of this study is to describe the implementation of learning from home policies with the new normal order in elementary schools in Bulak District, Surabaya City. The theory used in this research is the theory of implementation model by Edward III. This type of research uses descriptive qualitative. The results of this study indicate that: (1) Communication has been implemented well; (2) Resources are well implemented but staff are not sufficient; (3) The disposition has been implemented very well; (4) The bureaucratic structure is well implemented.